Dependence of neutrons generated by 7Li(p, n) reaction on Li thickness under free-air condition in accelerator-based boron neutron capture therapy system employing solid-state Li target. (February 2019) - Nakamura, Satoshi; Igaki, Hiroshi; Okamoto, Hiroyuki; Wakita, Akihisa; Ito, Masashi; Imamichi, Shoji; Nishioka, Shie; Iijima, Kotaro; Nakayama, Hiroki; Takemori, Mihiro; Kobayashi, Kazuma; Abe, Yoshihisa; et al.
Highlights: The accelerator-based BNCT system with a solid state-Li target has disadvantages. One of the main disadvantages is a degradation of the Li target. The degradation affects the number of neutrons and the neutron energy spectra. Effect of the degradation to the absorbed dose in BNCT was not observed. Abstract: Purpose: An accelerator-based boron neutron capture therapy (BNCT) system with a solid-state Li target is reported to have degradation of the Li target. The degradation reduces the Li thickness, which may change spectra of the generated neutrons corresponding to the Li thickness. This study aims to examine the relationship between the Li thickness and the generated neutrons and to investigate the effects of the Li thickness on the absorbed dose in BNCT. Method: The neutron energy spectra were calculated via Monte Carlo simulation for Li thicknesses ranging from 20 to 150 μm. Using the system, the saturated radioactivity of gold induced by reactions between 197 Au and the generated neutrons was evaluated with the simulation and the measurement, and those were compared. Additionally, for each Li thickness, the saturated radioactivity was compared with the number of generated neutrons. The absorbed doses delivered by 10 B(n, α) 7 Li, 14 N(n, p) 14 C, 1 H(n, g) 2 H, and (n, n′) reactions in water were also calculated for each Li thickness. Results: The measurement and simulation indicated a reduction in the number of neutrons due to the degradation of the Li target. However, the absorbed doses were comparable for each Li thickness when the requisite number of neutrons for BNCT was delivered. Additionally, the saturated radioactivity of 198 Au could be a surrogate for the number of neutrons even if the Li thickness was varied. Conclusions: No notable effect to the absorbed dose was observed when required neutron fluence was delivered in the BNCT even if the degradation of the Li was observed.